Urgensi Desain Pembelajaran Berbasis Soft Skill di Perguruan Tinggi - Syahdara Anisa Makruf (Cendekia: Kependidikan dan Kemasyarakatan, 2017)
Learning based on soft skill and hard skill is essential in college. The problem that often arises is that there are still many lecturers who design their learning based on hard skills only. This is because some lecturers do not understand the importance of learning based on soft skill. This research uses library research approach to examine how iurgency of learning design based on soft skill in college. The result shows that the design of learning based on soft skill in college aims to realize the students who believe in God and become an independent and responsible person. Thus, learning based on soft skill is relevance because it is a capital for students to be able to manage themselves and respect in social life. The lecturers could teach soft skill values in three ways, namely: lecturer role model, message of the week, and hidden curriculum. إن التدريس على أساس المهارات الناعمة والمهارات الصعبة أمر أساسي في المستوى الجامعي. والمشكلة هي لايزال كثير من المدرسين صمّموا تدريسهم على أساس المهارات الصعبة  فقط. هذا لأن بعضا منهم لم يفهموا جيّدا معنى " التعليم على أساس المهارات الناعمة ". حاول هذا البحث – بمدخل البحث المكتبي – الدراسة العميفة كيف تصميم التعليم على أساس المهارات الناعمة وأهميّته في الجامعات. دلّت نتائج البحث على أن تصميم التعليم على أساس المهارات الناعمة في الجامعات هو بهدف إيجاد الطلاب المؤمنين بالله، والمتقين الله، والمتخلقين ليكونوا أشخاصا معتمدين على أنفسهم وذوى المسؤولية. بهذا كان التعليم على أساس المهارات الناعمة مناسب ومهمّ ليكون عدّة للطلاب ليكونوا قادرين على إدارة أنفسهم ولهم وعي في الحياة مع مجتمعهم. ويمكن نقل قيم المهارات الناعمة من المحاضر إلى الطلاب عن طرق ثلاث وهي : 1) مثالية المحاضر، 2) الرسائل الأسبوعية، 3) المنهج الدراسي الخفيّ.